The effect of copper mining on vegetation disturbances in and out of Oyu Tolgoi mining site - Amarsanaa, Sainchuluu; Lkhagva, Ariuntsetseg; Tsooj, Bolormaa; Jargalsaikhan, Erdenechandmani (Proceedings of the Mongolian Academy of Sciences, 2022)
Since 2005, the mining sector has been a vital part of Mongolia's economy. This sector is one of Mongolia's most important sources of revenue. Primary outputs of Mongolia's mining industry are copper, gold, and coal. On the other hand, mining has a negative impact on the environment causing soil erosion, noise pollution, water pollution, and biodiversity loss. The Oyu Tolgoi copper mine is located in a semi-arid zone in the Mongolian Gobi. The impact of mining was investigated by sampling eight plots both in and out of this giant mining site. Vegetative cover, species richness, biomass, and basal gap of perennial plants were compared within and outside the perimeter of the Oyu Tolgoi mining site. The mining sites have a harmful impact on the environment. According to our findings vegetation cover, species richness, biomass, and perennial plant gaps were not different between the paired plots outside and inside of the mining site. Mining activities had little effect on vegetation, according to the findings.